Model Pembelajaran Inkuiri dan Discovery Learning dalam Administrasi Pendidikan - Khoirunisa; Adelia Yuliani; Siti Alfiah; Eva Iryani (Jurnal Ilmiah Kanderang Tingang, 2026)
The shift in the educational paradigm toward a student-centered approach demands innovation in teaching strategies, including in the field of Educational Administration. This article examines two innovative learning models, the Inquiry Learning Model and Discovery Learning, in depth, and their relevance and application in the context of Educational Administration. Based on constructivist theory, these two models aim not only to transfer theoretical knowledge but also to train students to develop critical, analytical, and creative thinking skills, as well as problem-solving skills essential for an educational administrator. Through a comprehensive literature review, this article outlines the nature, principles, characteristics, implementation steps, and advantages and disadvantages of each model. Furthermore, this article presents concrete examples of the application of both models in teaching Educational Administration courses, such as through real-world case studies and exploration of school financial data. An analysis of the supporting and inhibiting factors for their implementation is also presented, emphasizing the crucial role of educational administrators in creating a supportive ecosystem. It concludes that mastery and application of the Inquiry Learning and Discovery Learning models are important indicators of the quality of an institution's educational administration in preparing competent, adaptive graduates who are ready to face the dynamics of the 21st-century education world.